Efeito antioxidante de uma nova classe de compostos teluroacetilenos: estudos in vitro e in vivo - Souza, Ana Cristina Guerra de (2010)
Organotellurium compounds have been reported as antioxidants in several models of oxidative stress, especially in the brain. This study investigated the effect of telluroacetylenes a-d on pharmacological assays in vitro. A second objective of this study was to investigate the antioxidant action of compound b against the oxidative damage induced by sodium nitroprusside (SNP) in mouse brain. In in vitro experiments, lipid peroxidation (LP) and protein carbonyl (PC) levels and δ-aminolevulinate dehydratase (δ-ALA-D) activity were carried out in rat brain homogenate. The mechanisms involved in the antioxidant effect of telluroacetylenes a-d were studied. The glutathione peroxidase (GPx)-like activity, glutathione S-transferase (GST)-like activity and the protection against Fe2+ autooxidation were determined. Furthermore, the scavenger effect of 2,2 -diphenyl-1-picrylhydrazyl (DPPH ) and 2,2 -azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS +) radicals and hydrogen peroxide (H2O2) were investigated. In in vivo experiments, mice received SNP (0.335 μmol per site) intra cerebroventricular (i.c.v.) thirty minutes after oral administration of telluroacetylene b (10 mg/kg). After 1 h, animals were euthanized. The levels of LP and δ- ALA-D, GPx, GST, catalase (CAT) and glutathione reductase (GR) activities were carried out in mouse brain homogenate. Telluroacetylenes a-d, at low μM range, reduced LP and PC levels in rat brain homogenate. Telluroacetylenes a-d showed effect of scavenging DPPH and ABTS + radicals and H2O2. However the compounds had no GPx-like and GST-like activities or protected against Fe2+ autooxidation, discarding that these mechanisms are involved in the antioxidant effect of telluroacetylenes a-d. δ-ALA-D activity was inhibited by telluroacetylenes a-d, at high μM range, in rat brain homogenate. In the in vivo experiments, brains of mice treated with SNP showed an increase in LP and the reduction in δ-ALA-D, GR and GST activities. Telluroacetylene b protected against the oxidative stress caused by SNP in brain of mice. Moreover, telluroacetylene b incresead per se GPx activity in brains of mice. The results support an antioxidant effect of telluroacetylenes a-d in vitro. Telluroacetylene b protected against oxidative damage caused by SNP in mouse brain, suggesting an antioxidant effect of this compound in vivo.